Management der IUGR zwischen Praxis und Klinik - Kehl, Sven (gynäkologische praxis, 2020)
Diagnosis of IUGR is often late or IUGR is not recognized which results in high mortality and morbidity of this complication . Sonography and Doppler measurements have to be undertaken when IUGR is suspected . In IUGR, regular checkups in an outpatient or inpatient setting are mandatory . Timing of early delivery is the main goal in the management of IUGR . Gestational age has to be considered especially in preterm delivery . Doppler measurements are especially helpful to predict adverse perinatal outcome . Despite the increased risks, caesarean section is not the delivery of choice . Vaginal delivery is possible when intrapartum monitoring is conducted . A perinatal center with neonatal intensive care unit and a skilled staff to handle potential complications immediately and continuously is the place to be when IUGR is known .
CRIS-Team Scopus Importer:2020-10-09
Keywords: Doppler; IUGR; Management; SGA